Method to enhance atomic-layer deposition of tungsten-nitride diffusion barrier for Cu interconnect - Sim, HS; Kim, SI; Kim, YT (A V S AMER INST PHYSICS, 2003)
We have suggested an atomic layer deposition (ALD) method for preparing W-N films on Si and non-Si surfaces by using WF6 and NH3 . It is very difficult to deposit W-N films with sequential exposures of WF6 and NH3 because WF6 either reacts with Si quickly due to the catalytic reaction of Si, forming a thick W layer instead of the W-N, or does not adhere to the non-Si surface at 200-400 degreesC. In this method, during the ALD cycle we have introduced NH3 gas with pulse rf power, resulting in a NH3 pulse plasma that modified Si and SiO2 surfaces to become Si-N and Si-O-N surfaces. With this method, we can obtain a uniformly distributed N concentration in the W-N films deposited on the Si and non-Si surfaces with the deposition rate of similar to2.2 Angstrom/cycle at 350 degreesC. As a diffusion barrier for the Cu interconnect, high-resolution transmission electronic microscopy reveals that after annealing at 700 degreesC for 30 min, 22 nm thick W-N successfully prevents Cu diffusion. (C) 2003 American Vacuum Society.
Keywords: FILMS; SILICON